Image Watermarking for Mobile Device - Abdul-Jabbar, A.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The mobile services are the most important media between many of telecommunication means such as the Internet and Telephone networks, And thatis be cause of its advantage represented by the high availability and independence of physical location and time,Therefore,  the need to protect the mobile information appeared against the changing and the misuse especially with the rapid and wide grow of  the mobile network and its wide usage through  different types  of information such as messages, images and videos. The proposed system uses the watermark as tool to protect images on a mobile device by registering them on a proposed watermarking server. This server allows the owner to protect his images by using invisible watermarking. Also the user can prove his ownership to the images by the server which work as on  electronic court.